You are on page 1of 4

Solutions Assignment No.

1. (a) Yes. A matrix is Hermitian if it is equal to the conjugate of its transpose.


(b) The characteristic equation for E follows from det (H − EI) = −E 2 (E − 5) =
0. The eigenvalues are then E = 5, and a degenerate pair with E = 0. The
normalized eigenvectors corresponding to E = 5, E = 0, and E = 0 are:
     
1 0 2i
1 1
√  0 ,  1 , √  0 ,
5 2i 0 5 1
respectively. We can construct U † using the eigenvectors as the columns:
 1 

5
0 √2i5
.
U† =  0 1 0  .
2i

5
0 √15

The diagonalized Hamiltonian is then U HU † , which has the eigenvalues {5, 0, 0}


along the diagonal, and is 0 elsewhere.
2. (a) Consider
[x, [H, x]] = [x, Hx − xH] = 2xHx − x2 H − Hx2 .
For the last two terms, the ground state matrix element can be written as
⟨E0 |x2 H + Hx2 |E0 ⟩ = 2E0 ⟨E0 |x2 |E0 ⟩

= 2E0 ⟨E0 |x|Ej ⟩⟨Ej |x|E0 ⟩
j

= 2E0 |xj0 |2 .
j

Furthermore,

2⟨E0 |xHx|E0 ⟩ = 2 ⟨E0 |x|Ej ⟩⟨Ej |H|Ej ⟩⟨Ej |x|E0 ⟩
j

= 2 ⟨E0 |x|Ej ⟩Ej ⟨Ej |x|E0 ⟩
j

= 2 Ej |xj0 |2 .
j

Therefore
1 ∑
⟨E0 |[x, [H, x]]|E0 ⟩ = |xj0 |2 (Ej − E0 ) .
2 j

(b) Now
1 2 iℏ
[H, x] = [p , x] = − p
2m m
1 iℏ ℏ2
∴ [x, [H, x]] = − [x, p] = .
2 m 2m

1
3. For the even-parity state, for x > 0 we have the following solutions to the Schroedinger
equation in the regions x < d and x > d:
{
A (eκx + e−κx ) , 0 < x < d
ψ(x) =
e−κx , x>d

The wavefunction ψ(x) must be continuous at x = d. The discontinuity in the deriva-


tive ψ ′ (x) is found by integrating the Schroedinger equation over an infinitesimal in-
terval d − ϵ < x < d + ϵ, giving
2maV0
ψ ′ (d + ϵ) − ψ ′ (d − ϵ) = − ψ(d).
ℏ2
Isolating the x < d from the x > d terms, we find the following two equations:
( )
A eκd + e−κd = e−κd (1)
( )
( κd −κd
) −κd 2maV0
κA e − e = e −κ + . (2)
ℏ2

Dividing Eq. (2) by Eq. (1) gives

2maV0
κ tanh(κd) = −κ + ,
ℏ2
which is equivalent to the required result.
For the odd parity state, for x > 0 we have
{
A (eκx − e−κx ) , 0 < x < d
ψ(x) =
e−κx , x>d

As above, the continuity and discontinuity conditions at x = d lead to the following


two equations:
( )
A eκd − e−κd = e−κd (3)
( )
( ) 2maV0
κA eκd + e−κd = e−κd −κ + . (4)
ℏ2

Dividing Eq. (4) by Eq. (3) gives

2maV0
κ coth(κd) = −κ + ,
ℏ2
as required.

2
4. (a) We have
xn0 † xn0 [ † n ]
x̂n = n/2
(â + â) n
= n/2
(â ) + (↠)n−1 â + . . . + ↠ân−1 + ân ,
2 2
with all possible orderings, since ↠and â don’t commute. There is only one term
with ân . We also have
√ √
â|En ⟩ = n|En−1 ⟩ . ∴ ân |En ⟩ = n!|E0 ⟩ .
For the matrix element ⟨E0 |x̂n |En ⟩ only the ân term has a non-zero matrix ele-
ment, so that
xn0
⟨E0 |x̂n |En ⟩ = n/2 ⟨E0 |ân |En ⟩
2 √
xn0 √ n!
= n/2 n! ⟨E0 |E0 ⟩ = n/2 xn0 .
2 2
(b) To show
[ ]
â, (â + ↠)n = n(â + ↠)n−1
we can use induction. Clearly it is true for n = 1 based on the fundamental
relation â↠= ↠â + 1. Assume it is true for some n. Then
[ ]
â, (â + ↠)n+1 = â(â + ↠)(â + ↠)n − (â + ↠)n+1 â
( )
= (â + ↠)â + 1 (â + ↠)n − (â + ↠)n+1 â
[ ]
= â, (â + ↠)n + (â + ↠)n
= (n − 1)(â + ↠)n + (â + ↠)n
= n(â + ↠)n .
Now discarding terms involving ⟨E0 |↠and â|E0 ⟩, we can manipulate the expec-
tation value
⟨E0 |(â + ↠)2k |E0 ⟩ = ⟨E0 |â(â + ↠)2k−1 |E0 ⟩
= (2k − 1)⟨E0 |(â + ↠)2k−2 |E0 ⟩
= (2k − 1)(2k − 3) · · · (3)(1)
(2k)!
=
(2k)(2k − 2) · · · (2)
(2k)!
= .
2k k!
5. We have â↠|E0 ⟩ = (↠â + 1)|E0 ⟩ = |E0 ⟩. Proceed by induction. Suppose
â(↠)n |E0 ⟩ = n(↠)n−1 |E0 ⟩,
which is true for n = 1. Then
â(↠)n+1 |E0 ⟩ =â↠(↠)n |E0 ⟩
=(↠â + 1)(↠)n |E0 ⟩
=↠n(↠)n−1 |E0 ⟩ + (↠)n |E0 ⟩
=(n + 1)(↠)n |E0 ⟩
d † n+1
= (â ) |E0 ⟩.
dâ†

3
If we expand the function f (↠) in a Taylor series



f (↠) = cn (↠)n ,
n=0

then clearly



âf (â )|E0 ⟩ = cn â(↠)n |E0 ⟩
n=0


d † n
= cn (â ) |E0 ⟩
n=0
dâ†
d
= †
f (↠)|E0 ⟩.
dâ